THE ROLE OF JOURNALISTS IN UNCOVERING THE MURDER OF BRIGADIER JOSHUA - Eldy Haniel Rauan; Saeful Mujab; Metha Madonna (International Journal of Social Science, 2023)
This research aims to determine the role of journalists as part of the supervisory pillar of the authorities, in reporting on the murder case of Brigadier Joshua. Journalists play a role in providing accurate information regarding the actual situation, in this case uncovering the murder of Brigadier Joshua. So that the tangled thread of the murder case of Brigadier Joshua committed by his superiors can be revealed. To answer this problem, researchers used qualitative research methods and conducted in-depth interviews using a phenomenological approach. The results of the research show that the initial information conveyed by the Indonesian National Police (Polri) regarding the death of Brigadier Yosua gave rise to skepticism among journalists so this information was not immediately accepted. Regarding this matter, journalists stimulate the public by using diction, for example with the word "irregularities". Journalists who initially only conveyed information and tended to be passive, became active players through verification and independent investigations carried out to take various angles or framing of the case in question so that they were able to move the parties to react and make this case an important issue within the National Police that must be resolved immediately, and demands the government to enforce the law as fairly as possible